Adenoid cystic carcinoma right breast: a rare case report - V., Shruthikamal; S., Reshma; S., Rajesh (International Surgery Journal, 2017)
Adenoid Cystic carcinoma of the breast is a rare neoplasm accounting for 0.1% of breast carcinomas, and presenting most commonly as a painful breast lump. In contrast to the aggressive nature of adenoid cystic carcinoma at other sites, adenoid cystic carcinoma of the breast has a favourable prognosis, lymph node involvement or distant metastases seldom occur. Treatment is basically of modified radical mastectomy. Chemotherapy, radio therapy and hormonal treatment have been infrequently used. We report a case of 60 years old woman with adenoid cystic carcinoma of the right breast managed with MRM.